PWWP2B Fine‐Tunes Adipose Thermogenesis by Stabilizing HDACs in a NuRD Subcomplex. Issue 16 (27th June 2021) - Yan, Linyu; Jin, Weiwei; Zhao, Qingwen; Cui, Xuan; Shi, Ting; Xu, Yingjiang; Li, Feiyan; Jin, Wenfang; Zhang, Zhe; Zhang, Zhao; Tang, Qi‐Qun; Pan, Dongning
Abstract: Histone deacetylases (HDACs) are widely involved in many biological processes, as well as in control of brown and beige adipose physiology, but the precise molecular mechanisms by which HDACs are assembled into transcriptional machinery to fine‐tune thermogenic program remain ill‐defined. PWWP domain containing 2b (PWWP2B), which is identified as a component of the nucleosome remodeling and deacetylation complex (NuRD), interacts and stabilizes HDAC1/2 at the thermogenic gene promoters to suppress their expression. Ablation of Pwwp2b promotes adipocyte thermogenesis and ameliorates diet‐induced obesity in vivo. Intriguingly, Pwwp2b is not only a brown fat‐enriched gene but also dramatically induced by cold and sympathetic stimulation, which may serve as a physiological brake to avoid over‐activation of thermogenesis in brown and beige fat cells. Abstract : This work reveals a negative regulation mechanism to fine‐tune adipocyte thermogenesis, and highlights PWWP domain containing 2b (PWWP2B) as an intrinsic brake to keep thermogenic activity appropriately. PWWP2B stabilizes HDAC1/2 in a NuRD subcomplex, and promotes NuRD‐mediated deacetylation on thermogenic gene promoters. PWWP2B‐HDACs coordinate to prevent dissipating too much energy from activation of thermogenic program.